PENGARUH KOMPETENSI, INDEPENDENSI DAN MOTIVASI TERHADAP KUALITAS AUDIT APARAT INSPEKTORAT PADA PEMERINTAH KOTA MEDAN - Lutfriansyah Lutfriansyah (Universitas Medan Area, 2016)
This study examined the effect of competence, independence and motivation to audit quality in inspectorate officials in the city government field, a phenomenon that occurs in the city inspectorate field are their findings that should be discovered and disclosed by the inspectorate but not found by the Inspectorate but found by the BPK. The population of this study was 32 officers inspectorate, and the sampling technique used is saturated sample, thus the total sample of 32 people. The data used is primary data, and a model of data analysis used is multiple regression analysis and classical assumption test. The results of this study indicate that partial competence positive effect on audit quality, independence, positive effect on audit quality, motivation positive effect on audit quality and competence, independence and motivation simultaneously affect the quality of the audit